Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2023)
Table of Content:1. The impact of applying lean manufacturing systems on reducing costs of production companies in the Kingdom of Saudi Arabia for the year of 2022Dr. Huda Ibrahim Alsayed2. The impact of Greek thought on the intellectual renaissance in EuropeMr. Mahmoud Gawdat Qabaha3. An Organizational Culture and Its Relationship to the Job Performance of the workers - Applied Study on the Public for Telecommunications Corporation in Sana'aCo-Prof. Abdul-Hadi Hussain Al-Hamdani4. Monitoring The Performance of the Palestinian Security Apparatuses and its Role in Strengthen Freedom and Achieving Civil PeaceMr. Basem Salem Marshoud5. Mining in big data and its impact on decision-making from the point of view of managers and heads of departments of administrative units in the Ministry of Health in the Kingdom of Saudi ArabiaCo-Prof. Abdullah Ali Saeed Alqahtani6. Methods of Proof and Usage in Proof of parentage in the Islamic Fiqh, and the Jordanian Personal Status Law, DNA as an ExampleDr. Rasha Mohammed Almarafe, Prof. Hani Suleiman Al-Taimat7. Reality of job burnout among the employees of the National Bank of Saudi Arabia in KSAMrs. Mariam Abdullah Al-Zahrani
Keywords: Journal of Economic, Administrative and Legal Sciences